Extraction of beta-carotene from carrot via soxhlet extraction method - Mohamad Sazwan, Ismail (2013)
Extraction of carotene from carrot (Daucus Carota.L) using Soxhlet extraction method was done by using different solvent and time. Beta-carotene is the highest constituents in carotene. Fresh carrots are used as sample in this study. The effect of different parameters, which are type of solvents and duration of extraction time. Three types of solvents are used in this research which are acetone, ethanol, and 2-propanol. While, the duration of extraction time used are 2, 4, 6, and 8 hours. The overall process of this research involves four major steps which are sample preparation, extraction of carotene compound by using Soxhlet extraction, solvent separation of extracted compound by using rotary evaporator and analysis of carotene yield by using HPLC. When separated the desired compound from solvent, set the evaporator temperature at the boiling point of the solvent. The samples is then need to be filter first for the purpose of HPLC. The LC-18 is use as our HPLC column. The peak area for acetone is 19.7714%, 11.7953% for ethanol and 11.9622% for 2-propanol. The optimum extraction time for acetone is 6 hours. So, as a nutshell acetone is the best solvent with the optimum extraction time of 6 hours